Conformational control of cofactors in nature – the influence of protein-induced macrocycle distortion on the biological function of tetrapyrroles. Issue 96 (20th October 2015) - Senge, Mathias O.; MacGowan, Stuart A.; O'Brien, Jessica M.
Abstract : The biological function of tetrapyrroles and their use in designer proteins is critically dependent on their conformational flexibility. Abstract : Tetrapyrrole-containing proteins are one of the most fundamental classes of enzymes in nature and it remains an open question to give a chemical rationale for the multitude of biological reactions that can be catalyzed by these pigment–protein complexes. There are many fundamental processes where the same ( i.e., chemically identical) porphyrin cofactor is involved in chemically quite distinct reactions. For example, heme is the active cofactor for oxygen transport and storage (hemoglobin, myoglobin) and for the incorporation of molecular oxygen in organic substrates (cytochrome P450 ). It is involved in the terminal oxidation (cytochrome c oxidase) and the metabolism of H2 O2 (catalases and peroxidases) and catalyzes various electron transfer reactions in cytochromes. Likewise, in photosynthesis the same chlorophyll cofactor may function as a reaction center pigment (charge separation) or as an accessory pigment (exciton transfer) in light harvesting complexes ( e.g., chlorophyll a). Whilst differences in the apoprotein sequences alone cannot explain the often drastic differences in physicochemical properties encountered for the same cofactor in diverse protein complexes, a critical factor for all biological functions must be the close structural interplay between bound cofactors and the respective apoprotein in addition to factors such as hydrogen bonding or electronic effects. Here, we explore how nature can use the same chemical molecule as a cofactor for chemically distinct reactions using the concept of conformational flexibility of tetrapyrroles. The multifaceted roles of tetrapyrroles are discussed in the context of the current knowledge on distorted porphyrins. Contemporary analytical methods now allow a more quantitative look at cofactors in protein complexes and the development of the field is illustrated by case studies on hemeproteins and photosynthetic complexes. Specific tetrapyrrole conformations are now used to prepare bioengineered designer proteins with specific catalytic or photochemical properties.